A de novo Synthesis of Oxindoles from Cyclohexanone-Derived γ-Keto-Ester Acceptors Using a Desaturative Amination–Cyclization Approach - Caldora, Henry P.; Govaerts, Sebastian; Dighe, Shashikant U.; Turner, Oliver J.; Leonori, Daniele (Synthesis, 2021)
Here we report a desaturative approach for oxindole synthesis. This method uses simple ethyl 2-(2-oxocyclohexyl)acetates and primary amine building blocks as coupling partners. A dual photoredox–cobalt manifold is used to generate a secondary aniline that, upon heating, cyclizes with the pendent ester functionality. The process operates under mild conditions and was applied to the modification of several amino acids, the blockbuster drug mexiletine, as well as the formation of dihydroquinolinones.
Keywords: photoredox; cobalt catalysis; dehydrogenative amination; late-stage modification; amino acids; oxindole